Pathology of Tourist Attraction Problems in St. Mary Church of Urmia - AZIZZADEH, Fariba (Journal of Environmental Management and Tourism, 2020)
St. Mary Church of Urmia is ranked second in the world in terms of age. It has not been successful in attracting international tourists. This study is attempted to investigate the problems of tourist attraction for this church. The present study uses an interpretive paradigm and a qualitative research method in which the participants were 5 individuals from the target community of Christians working there. The tool used in this study was semi-structured interview (open-ended questions). Interaction between the researcher and the respondent as well as feedback from the participants has been used to ensure reliability. The information was analyzed using the thematic analysis method as well as during the three-step grounded coding (open, axial, and selective). According to the views of the participant, the 8 issues of the Ministry of Guidance on the issue of Christianity propagation, physical change of the church and the construction of a gable roof on it, the failure of Christians to propagate this church, a long-term bureaucracy of the Ministry of Guidance, the distance from Urmia to other tourist cities, issues related to restrictions on freedom and coverage in Iran, political issues and the effects of sanctions and inappropriate weather have been addressed.